A neuroprotective astrocyte state is induced by neuronal signal EphB1 but fails in ALS models. Issue 1 (December 2017) - Tyzack, Giulia; Hall, Claire; Sibley, Christopher; Cymes, Tomasz; Forostyak, Serhiy; Carlino, Giulia; Meyer, Ione F.; Schiavo, Giampietro; Zhang, Su-Chun; Gibbons, George; Newcombe, Jia; Patani, Rickie; et al.
Abstract Astrocyte responses to neuronal injury may be beneficial or detrimental to neuronal recovery, but the mechanisms that determine these different responses are poorly understood. Here we show that ephrin type-B receptor 1 (EphB1) is upregulated in injured motor neurons, which in turn can activate astrocytes through ephrin-B1-mediated stimulation of signal transducer and activator of transcription-3 (STAT3). Transcriptional analysis shows that EphB1 induces a protective and anti-inflammatory signature in astrocytes, partially linked to the STAT3 network. This is distinct from the response evoked by interleukin (IL)-6 that is known to induce both pro inflammatory and anti-inflammatory processes. Finally, we demonstrate that the EphB1–ephrin-B1 pathway is disrupted in human stem cell derived astrocyte and mouse models of amyotrophic lateral sclerosis (ALS). Our work identifies an early neuronal help-me signal that activates a neuroprotective astrocytic response, which fails in ALS, and therefore represents an attractive therapeutic target. Astrocytes can have protective or detrimental effects on neurons during injury, but the molecular mechanisms that determine these different states are unresolved. Here the authors identify a pathway via neuronal EphB1 that induces neuroprotective signalling in astrocytes through ephrin-B1 mediated STAT3 activation, which is impaired in models of amyotrophic lateral sclerosis.